Sprayable solutions containing sticky rice oil droplets reduce western flower thrips damage and induce changes in Chrysanthemum leaf chemistry - Bierman, Thijs V.; Fernandes, Hocelayne P.; Choi, Young H.; Seo, Sumin; Vrieling, Klaas; Macel, Mirka; Knegt, Bram; Kodger, Thomas E.; van Zwieten, Ralph; Klinkhamer, Peter G. L.; Bezemer, T. Martijn (Frontiers in Plant Science, 2025)
Thrips are one of the most challenging pests in agricultural crops, including Chrysanthemum. In this study we tested via two plant assays whether solutions containing sticky rice germ oil (RGO) droplets could effectively trap thrips and lower thrips damage on Chrysanthemum. In the first assay, we additionally assessed the metabolomic effects of these RGO droplet sprays and thrips presence on plant chemistry via 1H NMR and headspace GC-MS on multiple timepoints to investigate which plant metabolites were affected by spraying and their potential relation to plant resistance against thrips. In the second assay, we tested the individual RGO solution constituents against thrips. Our results suggested that the adhesive RGO droplets were not effective as a physical trap as only three out of 600 adult thrips were caught at the achieved coverage. However, average thrips damage was still reduced up to 50% and no negative effects on plant growth were observed up to 25 days. Results from the second plant assay indicated that the individual constituents of the solution containing RGO droplets may have direct effects against thrips. Metabolomics analysis of sprayed leaves via headspace GC-MS and 1H NMR indicated that fatty acids and several volatile compounds such as 4(10)-thujene (sabinene), eucalyptol, cis-4-thujanol, and isocaryophyllene were highest on day 10, while sucrose, malic acid, o-Cymene, and 3-Methyl-2-butenoic acid were highest on day 25. Plants with thrips showed higher flavonoid, carbohydrate and glutamine acetic acid levels, and lower fatty acids and malic acid levels. RGO application increased the levels of fatty acids and alcohols present on top of and inside the Chrysanthemum leaves, while decreasing the concentrations of volatile compounds such as eucalyptol, chrysanthenone and eugenol in the Chrysanthemum leaves. Most interestingly, the thrips effect on the plant metabolome was no longer visible in RGO treated plants at the later harvesttime, suggesting that RGO application may overrule or prevent the metabolomic effects of thrips infestation. In conclusion, our study provides new information on how the application of a new plant-based plant protection product affects insect herbivores and alters crop phytochemistry for improved herbivore resistance.